Electric-vehicle-enabled hosting capacity enhancement in distribution systems - Quijano, Darwin A. [UNESP]; Melgar-Dominguez, Ozy D.; Sabillon, Carlos; Padilha-Feltrin, Antonio [UNESP] (Elsevier, 2024)
This chapter presents and thoroughly explores the benefits brought about by a novel strategy, designed from the distribution system operator standpoint, aimed at estimating the distributed generation (DG) hosting capacity in electric distribution systems when controllable plug-in electric vehicles (EVs) are in place. The strategy determines the maximum wind and photovoltaic-based DG penetration by coordinating, on a forecast basis, the dispatch of EV aggregators, the operation of voltage regulation devices, and the active and reactive DG power injections. In this way, the broad casuistry resulting from the interaction of DGs with heterogeneous generation patterns and EVs is explored. The proposed approach advances system hosting capacities by leveraging controllable features of EVs while accounting for technical EV characteristics, driving behavior of EV owners, and EV energy requirements to accomplish their primary purpose. Presented as a two-stage stochastic mixed-integer linear programming problem (where the first stage maximizes the DG installed capacity and the second stage minimizes the energy losses), the proposed strategy extracts at its full the benefits of the flexibility associated with EVs. Further, uncertainties associated with renewable DG, conventional demand, and EV driving patterns are as well coped with via probability density functions.
Keywords: DG hosting capacity; Distribution systems; electric vehicles; stochastic optimization